The interactive effect of alcohol use and depressive symptoms in predicting couples' risk for intimate partner violence perpetration - O’Hair, Cayla M. (Journal of family violence, 2023)
Purpose: The prevalence of intimate partner violence (IPV) is alarmingly high among young adults. Alcohol use and depression have both been shown to increase risk for IPV. However, little is known about whether depression and alcohol may interact to predict IPV in couples. Methods: The current study utilized a sample of 81 racially and ethnically diverse young adult couples (91.4% between the ages of 18–24) to examine alcohol use and depressive symptoms as predictors of physical, sexual, and psychological IPV perpetration. Data were analyzed following an Actor-Partner Interdependence Model (APIM) framework, allowing for the examination of both actor and partner effects. Results: Results indicated that one’s own alcohol use was associated with an increase in one’s own psychological IPV perpetration, and one’s own depressive symptoms were associated with an increase in one’s own physical and psychological IPV perpetration. Although one’s partner’s alcohol use was associated with an increase in one’s own physical IPV perpetration on average, a marginally significant statistical interaction with one’s partner’s depression suggested this association was moderated, such that high levels of one’s partner’s depressive symptoms weakened the relationship between one’s partner’s alcohol use and one’s own physical IPV perpetration. Conclusions: Findings provide novel information on when depressive symptoms may be a risk factor for IPV in young adult couples.